English Grammar Learning Through Playful Activities: Suggestions for Primary School EAL Classrooms - Aguiar-Cruz, Gleice Kelly; Hitotuzi, Nilton Varela (Advances in Social Sciences Research Journal, 2023)
This article aims to propose a series of activities, integrating games and playful activities, as a teaching strategy for English grammar instruction in government-funded primary schools in Santarém, in the state of Pará, Brazil. These activities draw inspiration from Keith Folse’s work titled Keys to Teaching Grammar to English Language Learners: A Practical Handbook, which offers important guidance for designing effective grammar exercises. James Hoffman's research map (I-Chart) was adopted to summarize information from the materials used in the preparation of this article. Seven activities have been adapted from Folse’s book, with the anticipation that their implementation will contribute to enhancing pupils’ understanding of English language structures, while fostering increased motivation and active classroom engagement. Furthermore, it is hoped that English as an additional language teachers, upon reading this text, will feel inspired to teach the language through playful activities.